Features of blood supply of urethral tissues in women with primary urethral pain syndrome - A. S. Kuyarov; E. B. Kiseleva; L. A. Matveev; V. V. Dudenkova; О. S. Strelzova (Вестник урологии, 2023)
Introduction. Primary urethral pain syndrome (PUPS) is a part of chronic primary pelvic pain syndrome with predominant localisation of pain in the urethra. The pathogenesis of PUPS has not been adequately studied and there are no unified guidelines for the prevention and treatment of this condition. It is known that one of the main factors in the development of chronic pain is a violation of regional blood flow.Objective. To identify the features of blood supply of urethral tissues, as well as to assess the concomitant changes in the connective tissue in patients with PUPS.Materials & methods. The study included 98 patients: 78 patients with primary urethral pain syndrome (group "PUPS"), without clinical manifestations of inflammation; 20 patients with stones of the upper urinary tract without pyelonephritis, in which the urethra is taken as the norm (group "N"). The hemodynamics of the urethral tissues was studied using transvaginal ultrasound (TVUS) and laser Doppler flowmetry (LDF). Changes in the blood supply to organs often lead to disruption of tissue structure; therefore, in vivo cross-polarisation optical coherence tomography (CP OCT) and ex vivo nonlinear confocal microscopy were included in the study.Results. In the PUPS group, the LDF method revealed a violation of the neurogenic regulation of the tone of the microcirculatory vascular wall of the urethral tissues with a predominance of passive regulatory components. The analysis of the LDF parameters by the method of principal components made it possible to establish the division of data into several clusters, which indicates a different pathogenesis of microcirculation disorders in the tissues of the urethra. The TVUS method in the PUPS group revealed an increase in resistance to blood flow in the blood vessels of the urethra and paraurethral plexus, blood stasis in the veins of the small pelvis in 19% of patients. Violation of the urethral blood flow leads to structural changes in tissues: using nonlinear microscopy, it was found that with PUPS in the urethral connective tissue, collagen fibres are quantitatively larger relative to elastic ones, they are more uniform in thickness, and have a co-directional arrangement. These data correlate with the results of an intravital CP OCT study, during which fibrosis of the subepithelial connective tissue structures was revealed.Conclusion. TVUS and LDF made it possible to reveal the presence of microcirculatory and, as a result, structural changes in urethral tissues in vivo. The inclusion of these methods in the diagnostic algorithm will provide more information about the main links in the pathogenesis of PUPS.